High-Density Genetic Linkage Map Construction Using Whole-Genome Resequencing for Mapping QTLs of Resistance to Aspergillus flavus Infection in Peanut - Jiang, Yifei; Luo, Huaiyong; Yu, Bolun; Ding, Yingbin; Kang, Yanping; Huang, Li; Zhou, Xiaojing; Liu, Nian; Chen, Weigang; Guo, Jianbin; Huai, Dongxin; Lei, Yong; et al. (Frontiers in Plant Science, 2021)
Cultivated peanut (Arachis hypogaea L.), which is rich in edible oil and protein, is widely planted around the world as an oil and cash crop. However, aflatoxin contamination seriously affects the quality safety of peanut, hindering the development of peanut industry and threatening consumers’ health. Breeding peanut varieties with resistance to Aspergillus flavus infection is important for the control of aflatoxin contamination, and understanding of the genetic basis of resistance is vital to its genetic enhancement. In this study, we report the QTL mapping of resistance to A. flavus infection of a well-known resistant variety J11. A recombination inbred line (RIL) population was constructed by crossing a susceptible variety Zhonghua 16 and J11. Through whole-genome resequencing, a genetic linkage map was constructed with 2,802 recombination bins and an average inter-bin distance of 0.58 cM. Combined with phenotypic data of infection index in four consecutive years, six novel resistant QTLs were identified and they explained 5.03-10.87% phenotypic variances. The favorable alleles of five QTLs were from J11 while that of one QTL were from Zhonghua 16. The pyramiding of these favorable alleles significantly improved the resistance to A. flavus infection. These results could contribute greatly to understanding of genetic basis of A. flavus resistance and could be meaningful in further resistance improvement in peanut.